PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI MASALAH KENAKALAN SISWA DI MTS BABUSSALAM BANJAREJO PAGELARAN MALANG - Sholichah, Norma Ita (INTAJ : Jurnal Penelitian Ilmiah, 2019)
The focus of the problems in this study are: (1) the forms of student delinquency in MTs Babussalam; (2) the efforts of Islamic Education Teachers in overcoming student delinquency in MTs Babussalam; (3) the factors can influence student delinquency in MTs Babussalam. This research used is a qualitative descriptive approach through observation, interviews, and documentation. Then analyzing the data, reducing, and verifying. The results shows that the form of student delinquency in MTs Babussalam Banjarejo classified as minor violations often do not go to school, play truant in terms of half entering class hours and go home after breaking time, late, quarreling, or disorderly with rules existing schools.  The factors that influence student delinquency in MTs Babussalam Banjarejo include technological development; social factors including environmental influences and peer influences; and awareness factors. There are some efforts taken by the Islamic education teachers in overcoming student delinquency problems at MTs Babussalam Banjarejo, namely personal approach, coaching, habituation, and collaboration with related parties such as student guardians and boarding school administrators as parents' representatives for students who live in boarding schools.